2016
DOI: 10.1063/1.4940889
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced emission and photoconductivity due to photo-induced charge transfer from Au nanoislands to ZnO

Abstract: We report systematic studies based on photoluminescence, Hall, and photoconductivity measurements together with theoretical modeling in order to identify mechanisms for the photo-induced charge transfer effects in ZnO thin film incorporated with the Au nano-islands (AuNIs). Significant enhancement of near band edge emission and improvement in conductivity of ZnO/AuNIs samples after illumination are observed, which are attributed to the photo-induced hot electrons in Au which are then transferred into the condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Hence, the ZnO PL is of great interest and its enhancement is also important in order to develop efficient optoelectronic devices. Numerous studies have demonstrated the enhancement of both near band edge (NBE) and defect emissions using ZnO decorated with metallic NPs [ 92 93 ]. The study in [ 92 ] showed a PL enhancement of the Au–ZnO heterojunction system by an order of magnitude when ZnO thin films were incorporated with gold nanoislands.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the ZnO PL is of great interest and its enhancement is also important in order to develop efficient optoelectronic devices. Numerous studies have demonstrated the enhancement of both near band edge (NBE) and defect emissions using ZnO decorated with metallic NPs [ 92 93 ]. The study in [ 92 ] showed a PL enhancement of the Au–ZnO heterojunction system by an order of magnitude when ZnO thin films were incorporated with gold nanoislands.…”
Section: Reviewmentioning
confidence: 99%
“…Numerous studies have demonstrated the enhancement of both near band edge (NBE) and defect emissions using ZnO decorated with metallic NPs [ 92 93 ]. The study in [ 92 ] showed a PL enhancement of the Au–ZnO heterojunction system by an order of magnitude when ZnO thin films were incorporated with gold nanoislands. The enhancement is considered to be attributed to a hot carrier transfer from Au to ZnO.…”
Section: Reviewmentioning
confidence: 99%
“…21 Accordingly, among other n-type metal oxide materials used in inverted solar cells, zinc oxide (ZnO) has been extensively studied as a substitute to TiO 2 due to its similar electron affinity, relatively high electron mobility, high transparency, and versatile nanostructures. 22,23 For high performance inverted perovskite solar cell, the selection of the electron collection layer with hole blocking capability and low resistivity pathway for efficient electron extraction is necessary. ZnO have been demonstrated to be an effective electron collection material due to its various nanostructures that can be easily achieved by solution process for more efficient charge extraction and transport.…”
Section: Introductionmentioning
confidence: 99%
“…Although TiO 2 -based perovskite solar cells may pave the way to high PCE devices, several disadvantages of TiO 2 were reported such as low electron mobility and high annealing temperature (above 450 °C) to form a crystalline TiO 2 film in anatasephase . Accordingly, zinc oxide (ZnO) has been extensively studied as a substitute for TiO 2 due to its similar electron affinity, relatively high electron mobility, high transparency, and versatile nanostructures. …”
Section: Introductionmentioning
confidence: 99%
“…Excluding the exception of the report by Lin et al [16] indicating substantially pronounced CdS related defect luminescence in Au-CdS, and of the reports on Au-ZnO [17,18] such hot electron transfer is not observed to be responsible to enhance luminescence. Thereby, the basic understanding which can help to form the metal-semiconductor nanostructure with elevated PL efficiency is lacking and needs systematic studies to identify the physical mechanisms.…”
Section: Introductionmentioning
confidence: 75%